MULTI-OBJECTIVE MATHEMATICAL PROGRAMMING MODELS AS DECISION SUPPORT SYSTEM FOR PARK ROADS MANAGEMENT - Puang, Nathakitt; Yarwudhi, Chanchai; Prasomsin, Patsi (วารสารวนศาสตร์ไทย, 2022)
The park roads are built every year in the national parks of Thailand. New-built park roads are rarely based on sound road standards. The maximum gradient often exceeds allowable safety standards. A low road safety quality usually causes high road accidents. Presently, new park roads construction has high cost of investment and maintenance but relatively short life span of use. Excessive clearing, grubbing and tree felling usually causes large open areas which then damages the ecosystem. Therefore, a multi-objective criterion for park roads planning and design in National Parks of Thailand using multi goals programming was applied to minimize conflicting goals. The study models were applied to the Thai existing park road data in Khao Yai National Park. These developed mathematical models for park roads construction can be applied to control park roads design and construction in National Parks. The results indicated that the model of the less environmental impact criteria resulted in the highest cost of construction. While, the model of the maximum traveling safety and the minimum environment impact criteria resulted not much difference in construction cost. Thus, the decision maker of park road planning and design should take these two criteria into account in preparing the proposed Park Roads Standard for controlling park roads design and construction in national parks.